MEMBANGUN POLA RELASI KELUARGA BERBASIS KESETARAAN DAN KEADILAN GENDER - Siti Rofi’ah (MUWAZAH : jurnal kajian gender, 2015)
This study departs from the reality of patriarchal family relationship patterns that distinguish between the role of men (husbands) and women (wives) in the household, where the husband is the head of the family (public) and the wife is a housewife (domestic). Different patterns of family relationships, resulting in injustice and gender in equality. That condition would require the construction pattern of relationships base dongenderequality, to realize a gender partnership to wards a harmonious family. Construction pattern of gender relations gender equality, realized if there is cooperation and division of roles equal and fair between husband and wife, which refers to the planning and implementation of resource management family, so family members have roles in various activities (domestic, public, and social).